Respuesta :
Answer:
The value of r(s(3)) = -21
Step-by-step explanation:
It is given that,
r(x) = -2x + 1
s(x) = -x^2 + 2
To find the value of r(s(3))
s(x) = -x^2 + 2
s(3) = (-3)^2 + 2 [Substitute 3 instead of x]
= 9 + 2
= 11
Therefore s(3) = 11
r(x) = -2x + 1
r(s(3)) = r(11) [Substitute 11 instead of x]
= -2(11) + 1
= -22 + 1
= -21
Therefore the value of r(s(3)) = -21
Hello!
The answer is:
[tex]r(s(3))=15[/tex]
Why?
To solve the problem, first, we need to compose the functions, and then evaluate the obtained function. Composing function means evaluating a function into another function.
We have that:
[tex]f(g(x))=f(x)\circ g(x)[/tex]
From the statement we know the functions:
[tex]r(x)=-2x+1\\s(x)=-x^{2}+2[/tex]
We need to evaluate the function "s" into the function "r", so:
[tex]r(s(x))=-2(-x^2+2)+1\\\\r(s(x))=2x^{2}-4+1=2x^{2}-3[/tex]
Now, evaluating the function, we have:
[tex]r(s(3))=2(3)^{2}-3=2*9-2=18-3=15[/tex]
Have a nice day!